Comparison of single and double chest drains following pulmonary lobectomy - Ahmed Elmezayen; Ahmed Osama; Amal Said Elbendary; Abdelrahman Abdelbar (PLoS ONE, 2025)
Background Chest tubes are commonly used to empty the chest cavity after pulmonary lobectomy. Although two drains have traditionally been used to guarantee proper air and fluid evacuation, they frequently cause patients more pain and lengthen their hospital stays. This study set out to compare the effectiveness of using a single chest drain versus using two chest drains after a pulmonary lobectomy. Methods This retrospective trial was performed on 50 patients aged ≥18 years, both sexes, scheduled for Video-Assisted Thoracic Surgery (VATS) lobectomy. Patients were divided into two equal groups: Group S: single chest tube was used and Group D: double chest tubes were used. Results The duration of drainage was 3.32 ± 0.69 days in group S and was 4.2 ± 1.29 days in group D (P < 0.05). The amount of drainage was 593.64 ± 45.94 ml in group S and was 910.04 ± 71.42 ml in group D (P < 0.05). Assessment of the pain using the visual analog scale on second day was insignificantly different between both groups and was significantly lower at the second postoperative week in group S than in group D (P = 0.005). Length of hospital stays and complications (pneumonia, re-drainage, and persistent air leak (> 7 days)) were insignificantly different between both groups. Conclusions The effectiveness of inserting one chest tube following a pulmonary lobectomy is comparable to that of inserting two tubes. Furthermore, employing a single tube is more advantageous than two tubes, as it is associated with lower postoperative pain, duration and amount of drainage.